Antjie/Andries Somers: decoding the bodily inscriptions of a South African folklore character - Steenekamp, Maryne (My University, 2011)
The Antjie/Andries Somers folklore character invites different decodings since it has many different inscriptions. These proposed inscriptions aids this research project to explore the historical value this folklore character exhibits when compared to changes in South African social and political climates since the abolishment of the slave laws in 1834 until the present. This symbiotic relationship between culture and character, as well as the continuous restructuring of the character, is explored in an attempt to understand the changing fears and anxieties projected onto the Antjie/Andries Somers persona. This cultural icon also underwent a continuous number of different interpretations and manifestations as experienced by the Afrikaans speaking community during the past centuries. The body with relation to gender is another pivotal point regarding the Antjie/Andries Somers folklore as well as the question concerning the physical change from male to female. This relates to the controversy surrounding a woman as an object of “evil” that is investigated through the different mythologies regarding the origin of sin using the biblical character of Eve. These explorations of “evil” as an inscription on women is further examined against the backdrop of the patriarchal society and some of the many dominant religious practices from that time. Despite a vast archive of information on the various embodiments of Antjie/Andries Somers, the character as well as the embodiments, is still shrouded in mystery and the research project aims to provide information about some of these manifestations.
Keywords: Afrikaners; Folklore; South Africa